Characterization of the plastid genome of Cratoxylum species (Hypericaceae) and new insights into phylogenetic relationships - Runglawan, Sudmoon; Sanit, Kaewdaungdee; Tawatchai, Tanee; Pornnarong, Siripiyasing; Unchaleeporn, Ameamsri; Samsuddin, Ahmad Syazwan; Lee, Shiou Yih; Arunrat, Chaveerach (Springer Nature, 2022)
To expand the genomic information of Hypericaceae, particularly on Cratoxylum, we characterized seven novel complete plastid genomes (plastomes) of five Cratoxylum and two of its allied taxa, including C. arborescens, C. formosum subsp. formosum, C. formosum subsp. pruniflorum, C. maingayi, C. sumatranum, Hypericum hookerianum, and Triadenum breviflorum. For Cratoxylum, the plastomes ranged from 156,962 to 157,792 bp in length. Genomic structure and gene contents were observed in the five plastomes, and were comprised of 128-129 genes, which includes 83-84 protein-coding (CDS), 37 tRNA, and eight rRNA genes. The plastomes of H. hookerianum and T. breviflorum were 138,260 bp and 167,693 bp, respectively. A total of 110 and 127 genes included 72 and 82 CDS, 34 and 37 tRNA, as well as four and eight rRNA genes. The reconstruction of the phylogenetic trees using maximum likelihood (ML) and Bayesian inference (BI) trees based on the concatenated CDS and internal transcribed spacer (ITS) sequences that were analyzed separately have revealed the same topology structure at genus level; Cratoxylum is monophyletic. However, C. formosum subsp. pruniflorum was not clustered together with its origin, raising doubt that it should be treated as a distinct species, C. pruniflorum based on molecular evidence that was supported by morphological descriptions.